The Potential Role of Basophils in Urticaria - Takimoto-Ito, Riko; Ma, Ni; Kishimoto, Izumi; Kabashima, Kenji; Kambe, Naotomo (Frontiers in Immunology, 2022)
Urticaria is a symptom of acute skin allergies that is not clearly understood, but mast cell histamine is hypothesized to cause swelling and itching. Omalizumab, an anti-human IgE antibody that traps IgE and prevents its binding to high-affinity IgE receptors, is effective in treating urticaria. We recently experienced a case of urticaria refractory to antihistamine therapy in which the peripheral-blood basophil count responded to omalizumab therapy and its withdrawal. Furthermore, the peripheral-blood basophils showed an unexpected increase in the expression of a cell surface activation marker. This phenomenon has been reported by other analyses of basophil and mast cell dynamics during omalizumab treatment. Here, we analyze these observations and formulate a hypothesis for the role of basophils in urticaria. Specifically, that activated basophils migrate to the local skin area, lowering peripheral-blood counts, omalizumab therapy alters basophilic activity and causes their stay in the peripheral blood. We hope that our analysis will focus urticaria research on basophils and reveal new aspects of its pathogenesis.